MOLECULAR MODELING OF INOSINE 5'- MONOPHOSPHATE DEHYDROGENASE-II (HUMAN) STRUCTURE USING MD-SIMULATION METHOD - DEEPAK K. MISHRA; BISHNU P. MUKHOPADHYAY; HRIDOY R. BAIRAGYA (International Journal of Pharma and Bio Sciences, 2012)
Inosine 5’- monophosphate dehydrogenase of human (hIMPDH) is involved in GMP nucleotide biosynthesis pathway. Type II isoform is found in the human CML cells. Recently the enzyme is actively targeted for the development of anticancer and antleukemic agent. Till todate, a few low resolution 3D X-ray structures (contain 75% residues) of hIMPDH-II are available in PDB. For making a better three-dimensional model structure (with full sequence 514 residues) of hIMPDH-II molecular modeling methods have been attempted. Addition of 25% residues, energy minimization and 50 ns MD-simulation are successively followed for modeling of protein. The quality of final model structure has been validated by different modeling tools. The internal potential energy, stability free energy, solvation free energy, 3D profile quality index and Z-score values have clearly indicated the goodness of final refined model structure compared to hIMPDH-II X-ray structure. The model provides a detail stereochemical insight on the secondary structure and folding pattern of protein. The model may be used for docking studies (with different ligands) and insilico inhibitor design.